"Honramos o nome de Minas"? : sentidos identitários acionados pela comunicação organizacional do Clube Atlético Mineiro entre 2020 e 2023 - Luísa Almeida de Paula (2024)
In an increasingly interconnected and globalized world, identities are configured as a complex and dynamic mosaic, shaped by the various narratives that circulate and intertwine. In this context, soccer, a social and cultural phenomenon deeply affected by globalization, emerges as a valuable stage directly impacted by these dynamics, offering a rich lens for analyzing identity dynamics. Considering theoretical discussions on identities, globalization, and organizational communication, this research investigates how soccer is being affected by the process of globalization and the consequent challenges to identity, through a case study of Clube Atlético Mineiro's organizational communication. According to Hall (2006), globalization is intricately linked to the fragmentation of identities, impacting the identity formation process directly. Based on this assumption of shifting identities, the study aims to analyze how Atlético produces meanings associated with global, national, and regional identity in its organizational communication. Utilizing Laurence Bardin's Content Analysis methodology and Atlético's Instagram as a corpus, we seek to understand how the club constructs its image and produces meanings about these three identity categories: global, national, and regional.